2012
DOI: 10.3354/dao02524
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Anguillicoloides crassus and growth variation in migrant yellow-phase American eels of the upper Potomac River drainage

Abstract: Prevalence of the non-native swim bladder nematode Anguillicoloides crassus has recently increased in American eels from estuaries of the North American Atlantic coast, but little is known about parasite prevalence or conditions of previous infection in upstream migrant eels within upper watersheds. This study is the first to confirm presence of A. crassus in the upper Potomac River watershed. We estimated A. crassus prevalence during 3 time periods: September to October 2006 (5/143 eels, 3.5%), August to Octo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…But this criterion is not the best reflecting the eel pathogenicity due to the short life cycle of A. crassus , and severely damaged swimbladders are shown to harbor very few or even no living nematodes [42, 63]. Nevertheless, using the Swimbladder Degenerative Index, Lefebvre et al [44] recently demonstrated that the most affected eels had greater body length and mass (+11% and +41% respectively) than unaffected eels of the same age.…”
Section: Discussionmentioning
confidence: 99%
“…But this criterion is not the best reflecting the eel pathogenicity due to the short life cycle of A. crassus , and severely damaged swimbladders are shown to harbor very few or even no living nematodes [42, 63]. Nevertheless, using the Swimbladder Degenerative Index, Lefebvre et al [44] recently demonstrated that the most affected eels had greater body length and mass (+11% and +41% respectively) than unaffected eels of the same age.…”
Section: Discussionmentioning
confidence: 99%
“…Arguably, the migrating stage is the most important stage to study from a population viability perspective, rather than the body condition of earlier life stages. However, a study of American eel ( Anguilla rostrata ) found that eels with signs of previous infections with A. crassus (damage to the swim bladder) were shorter at a given age compared to eels that did not show any signs of previous infections (no damage to the swim bladder) (Zimmerman & Welsh, 2012). It is important to mention that our results showing no major observed effects of A. crassus concern only selected health indicators.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Atlantic sturgeon (Acipenser oxyrinchus) with skin and gill infections of the trematode, Nitzschia sturionis, lost weight compared to uninfected Atlantic sturgeon (Matsche et al 2010). Similarly, American eel (Anguilla rostrata) infected with the swim bladder nematode, Anguillicoloides crassus, had a lower length-at-age than uninfected eels (Zimmerman and Welsh 2012). Dermo disease in the eastern oyster can slow growth and cause a reduction in condition index of the oysters (Paynter and Burreson 1991).…”
Section: Growthmentioning
confidence: 99%
“…However, the upper watershed may be an important juvenile habitat for female American eels (Goodwin and Angermeier 2003). Therefore, an effect of A. crassus on growth could result in lower reproductive potential because American eels are semelparous with only one opportunity to spawn and smaller American eels would likely have lower fecundity (Zimmerman and Welsh 2012;Jessop 2018). During 2004During -2008 of Atlantic sturgeon from the Chesapeake Bay had infections of N. sturionis, which caused reduced growth (Matsche et al 2010).…”
Section: Interactions Among Mortality Growth and Reproductionmentioning
confidence: 99%